Differential hysteresis scanning of non-templated monomodal amorphous aerogels. Issue 9 (1st March 2021) - Taheri, Poroshat; Lang, John C.; Kenvin, Jeffrey; Kroll, Peter
Abstract : We perform Differential Hysteresis Scanning (DHS) Porosimetry of amorphous silicon oxycarbide aerogels to quantify hierarchical connectivity in these porous materials. Abstract : We perform Differential Hysteresis Scanning (DHS) Porosimetry of amorphous silicon oxycarbide aerogels to quantify hierarchical connectivity in these porous materials. We contrast high-resolution argon sorption scanning isotherms of samples obtained through a non-templated synthesis using different solvents, and characterize respective changes after calcination at 1000 °C. The multi-scan DHS data sets are analyzed through non-negative least-squares deconvolution using a kernel of theoretically derived isotherms for a selection of hierarchical geometries using non-local density functional theory (NL-DFT). We obtain two-dimensional contour plots that characterize mesopores according to the ratio between pore diameter and its connecting window. Combined information from DHS and complementary BET and BJH approaches reveals one system with monomodal distribution both in pore diameters and in window diameters. Hence, this amorphous material exhibits a uniformity usually only observed for crystalline systems. We demonstrate that DHS analysis provides quantitative data analyzing the hierarchical structure of mesoporous materials and unlocks pathways towards tailored materials with control of surface heterogeneity, localization, and sequential accessibility – even for amorphous systems.